Bersama UMNU Membangun Perekonomian Kerakyatan Menuju Indonesia Lebih Sejahtera - Suwarni, Titi; Laduni, Ade Irham; Sangadah, Umi (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2023)
Real work lectures were held in Karangasem Village, Kertanegara District, Purbalingga Regency for 40 days from 26 July to 7 September 2023. Karangasem Village was the selected village to be the target village for KKN. The wealth of village potential is one of the main objectives of implementing KKN to improve the quality of human resources (HR) and cultivate and develop local village potential. The process of initiating village observation KKN is to explore and identify village potential which is the main target in implementing KKN. These programs are designed sequentially, starting with discussions between the KKN group, village officials and the local community, especially those directly related to the program being designed. Implementation. The KKN program is implemented in a balanced manner, starting from planning, implementation and evaluation at the end of each program. The overall output of the KKN program includes community skills and supporting the development of human resources to increase the potential of local villages. Literacy programs are also implemented to develop quality human resources from an early age. In the MSME sector, digital marketing knowledge at the village level received active response and participation from residents of Karangasem Village, Kertanegara District, Purbalingga Regency, Central Java.Keywords: KKN, Karangasem Village, Village Potential